1, 2-Aminohalogenation of arynes with amines and organohalides. Issue 75 (2nd September 2019) - Li, Sheng-Jun; Han, Lu; Tian, Shi-Kai
Abstract : An unprecedented three-component reaction of amines, arynes, and organohalides provides convenient access to structurally diverse tertiary 2-haloanilines. Abstract : An unprecedented use of inexpensive organohalides as halogen electrophiles to trap the zwitterion intermediates generated from amines and arynes has been developed to access structurally diverse tertiary 2-haloanilines. Effective organohalides include carbon tetrachloride, hexachloroethane, N -chlorosuccinimide, carbon tetrabromide, fluorotribromomethane, N -bromosuccinimide, carbon tetraiodide, and N -iodosuccinimide.